ChemInform Abstract: One Pot Synthesis of Tetrasubstituted Thiophenes: [3 + 2] Annulation Strategy. Issue 35 (September 2015) - Sahu, Satya Narayan; Gupta, Maneesh Kumar; Singh, Surjeet; Yadav, Pratik; Panwar, Rahul; Kumar, Abhinav; Ram, Vishnu Ji; Kumar, Brijesh; Pratap, Ramendra
Abstract Base‐promoted ring opening of (methylthio)cyanopyranones by thioglycolate and sequential recyclization affords thiophenedicarboxylates in a one‐pot process.